Dialogue, science and academic writing [ - Livnat, Zohar (Dialogue studies, 2012)
This book investigates the dialogic nature of research articles from the perspective of discourse analysis, based on theories of dialogicity. It proposes a theoretical and applied framework for the understanding and exploration of scientific dialogicity. Focusing on some dialogic components, among them citations, concession, inclusive we and interrogatives, a combined model of scientific dialogicity is proposed, that reflects the place and role of various linguistic structures against the background of various theoretical approaches to dialogicity. Taking this combined model as a basis, the an